Larvicidal, Ovicidal, and Repellent Activities of Marine Sponge Cliona celata (Grant) Extracts against Culex quinquefasciatus Say and Aedes aegypti L. (Diptera: Culicidae). (27th November 2013) - Reegan, Appadurai Daniel; Kinsalin, Arokia Valan; Paulraj, Michael Gabriel; Ignacimuthu, Savarimuthu
Abstract : Solvent extracts of marine sponge Cliona celata (Grant) were screened for larvicidal, ovicidal, and repellent properties against the filarial vector Culex quinquefasciatus Say and dengue vector Aedes aegypti L. Larvicidal and ovicidal activities of hexane, ethyl acetate, and methanol extracts were tested in four different concentrations ranging as 62.5, 125, 250, and 500 ppm. Among the three solvent extracts of C. celata, methanol extract showed the highest larvicidal activity at 500 ppm against both mosquito species. The LC50 and LC90 values of C. celata methanol extract were recorded as 95.63 and 242.16 ppm against C. quinquefasciatus larvae and 158.40 and 780.16 ppm against A. aegypti larvae, respectively. Ovicidal activity was high in methanol extract, in which 100% ovicidal activity was recorded in C. quinquefasciatus, and 72% ovicidal activity was recorded in A. aegypti at 500 ppm. The hexane extract was found to be the most effective protectant against the adult mosquitoes of both species. The mean protection time recorded in hexane extract was up to 273 and 165 min at 5 mg/cm 2 dosage against C. quinquefasciatus and A. aegypti, respectively. Considering these bioactivities, C. celata could be used to obtain some novel pesticidal molecules.